Scarica il testo completo in PDF La controvertida prohibición de la blasfemia en la Constitución de la República de Irlanda (Stato, Chiese e pluralismo confessionale, 2018)
SUMARIO: 1. Introducción - 2. La prohibición de la blasfemia en el marco de una Constitución de clara inspiración católica - 3. El cuestionamiento de una norma de tan dudoso encaje en el sistema constitucional de derechos y libertades - 3.1. Las críticas en general al régimen constitucional de las confesiones religiosas - 3.2. La controversia específica en torno a la prohibición de la blasfemia en la Constitución irlandesa - 4. Algunas conclusiones y una razonable expectativa.The controversial offence of blasphemy in the Irish ConstitutionABSTRACT: As recently as June 2018 the Irish Government has approved a referendum to remove the offence of blasphemy from the Constitution; the referendum will be held in October this year. This paper briefly examines the historical and legal backgrounds of this controversial prohibition that survived the 1972 reform of the constitutional provisions in the field of Church and State that, among other aspects, conferred a special position to the Catholic Church, and it does so in order to underline the importance and the potential consequences of the proposed reform in case of an affirmative vote in the upcoming referendum. For this analysis the author gives prior consideration to the fundamental meaning and scope of the constitutional provisions currently in force in the area of Law and Religion and, once this framework is summarized, the paper turns to reflect primarily on the legal and judicial developments that have taken place in the last decades relating the offence of blasphemy in Irish Law.